Javanese Karawitan Extracurricular Learning In Elementary School Waluyorejo Puring Kebumen - Abie, Tian Faoztina; Widodo, Widodo; Wiyoso, Joko (Universitas Negeri Semarang, 2020)
Javanese Karawitan is a type of traditional music that is rarely used as extracurricular subjects in formal educational institutions. However, Sekolah Dasar (SD) Negeri 1 Waluyorejo, Puring District, Kebumen Regency, teaches Javanese music to extracurricular activities in the arts. The research method used was descriptive qualitative method. The data were obtained through observation techniques, interviews, and documentation. The results of the study were karawitan Jawa extracurricular at SD Negeri 1 Waluyorejo held three times a week. Javanese musical extracurricular learning is divided into two activities, namely routine and incidental learning. Provision of material from meetings 1 to 4, namely, (1) Gending Lancaran Gugur Gunung materials; (2) gending Lancaran Kebo Giro and Kebumen Binuko materials; (3) incorporation and application of training methods for nayaga and penggerong; (4) stabilization of nayaga and penggerong in playing the music and vocal Lancaran Kebo Giro and Kebumen Binuko materials which have been studied. Supporting factors are, (1) learning components that are mutually sustainable; (2) the moral support of the principal; and (3) the teachers and teams competence who are competent in their fields. The inhibiting factors are, (1) student interest still low in traditional arts; (2) teacher activities that conflict with practice scedule.